Advances in Mesopotamian medicine from Hammurabi to Hippocrates : proceedings of the International Conference "Oeil Malade et Mauvais Oeil", Collège de France, Paris, 23rd June 2006 - Attia, Annie.; Buisson, Gilles. (Cuneiform Monographs, 2009)
This volume, which originated with a conference at the Collège de France, comprises contributions by many of the leading researchers in Babylonian and Assyrian medicine. A wealth of topics are studied, including medical lexicography, prosopography, and technology, economic aspects of healing, and Mesopotamian influence on Greece. First-time editions of cuneiform medical tablets are presented. The volume will interest scholars in many branches of Assyriology, and also historians of Greek medicine. Contributors: Barbara Böck, Paul Demont, Jean-Marie Durand, Jeanette C. Fincke, Markham J. Geller, Nils. P. Heeßel, Marten Stol, Martin Worthington